2013
DOI: 10.1002/ejoc.201300246
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Michael‐Addition‐Initiated Three‐Component Reaction for the Regioselective Synthesis of Highly Functionalized Pyridines: Scope, Mechanistic Investigations and Applications

Abstract: A metal‐free and completely regioselective three‐component synthesis of highly functionalized pyridines from 1,3‐dicarbonyl derivatives and Michael acceptors has been achieved. Activated Michael acceptors, that is, β,γ‐unsaturated α‐oxo carbonyl derivatives, were utilized, allowing substitution at the 4‐position and remarkable functional diversity at the 2‐position of the pyridine ring. The scope and limitations of this environmentally friendly domino reaction are disclosed, with full experimental data, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 115 publications
0
22
0
Order By: Relevance
“…Later, two other important works 26,27 described a side-reaction from the Hantzsch(-like) reaction, and the mechanisms were based on these already shown in Schemes 21 and 23.…”
Section: Scheme 19mentioning
confidence: 98%
“…Later, two other important works 26,27 described a side-reaction from the Hantzsch(-like) reaction, and the mechanisms were based on these already shown in Schemes 21 and 23.…”
Section: Scheme 19mentioning
confidence: 98%
“…Recently, 1,3-dicarbonyl compounds are most extensively used for the synthesis of bioactive molecules [43][44][45]. It has been demonstrated that Knoevenagel [46][47][48] and Michael addition [49][50][51][52] reactions are involved in the synthesis of bioactive pyridine nucleus [49][50][51][52][53][54][55][56]. A number of homogeneous as well as heterogeneous catalysts [57][58][59][60][61][62][63][64][65][66][67][68] have been employed for the preparation of pyridines, dihydropyridines, and its analogs in diverse methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazolidines and pyrazolines are highly important compounds because of their wide presence in natural products and their bioactive and unique photophysical properties. [ 1–13 ] Therefore, many experimental and theoretical works have been dedicated to the efficient and stereoselective synthesis of pyrazolidine and pyrazoline compounds. [ 14–28 ] For instance, Kobayashi found that the Lewis acid chiral zirconium/BINOL complex can be used as an efficient catalyst to synthesize entioselectively pyrazolidine products via inter‐ or intra‐molecular [3+2] cycloaddition between hydrazones and alkenes.…”
Section: Introductionmentioning
confidence: 99%